Perancangan dan Pengembangan Video Company Profile Always Tour & Travel - Hendi Sama; Hartono Hartono (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
The development of information technology is very rapid regarding the promotion of a product to be introduced to the public, for that we need media that can promote it to the public. For this reason, the purpose of this activity is to create a company profile video to help Always Tour and Travel by introducing the services provided to the public. This video contains services sold by Always Tour and Travel. Data collection techniques used in making videos are interviews and observations. In this concept there are preproduction, then production, and also post-production stages. The application used by the author is Adobe Premiere Pro CC 2020. The end result is a company video Always Tour and Travel that has been uploaded on the Youtube platform. With the company profile video, it can increase sales and information to the public